2022
DOI: 10.1016/j.ces.2021.117334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molecular design parameters on plasticizer performance in poly(vinyl chloride): A comprehensive molecular simulation study

Abstract: Using all-atom molecular simulation, a wide range of plasticizers for poly(vinyl chlorid) (PVC), including ortho-and tere-phthalates, trimellitates, citrates, and various aliphatic dicarboxylates, are systematically studied. We focus on the e ects of plasticizer molecular structure on its performance, as measured by performance metrics including its thermodynamic compatibility with PVC, e ectiveness of reducing the material's Young's modulus, and migration rate in the PVC matrix. The wide variety of plasticize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
(141 reference statements)
0
10
0
Order By: Relevance
“…23,24 The results of theoretical and computational studies, including mesoscale and atomistic models of polymerplasticisers systems, have shown a change in the polymer T g due to a microscopic interplay between polymer and plasticisers. [25][26][27][28][29][30][31][32][33][34] A lattice model, called Limited Mobility, has been recently applied to study the influence of additives on the mobility of a matrix and the consequent change in the polymer T g . 26 The authors showed that both additive concentration and their molecular properties, such as stiffness, determine whether the T g of the system is raised or lowered respected to the pure material.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The results of theoretical and computational studies, including mesoscale and atomistic models of polymerplasticisers systems, have shown a change in the polymer T g due to a microscopic interplay between polymer and plasticisers. [25][26][27][28][29][30][31][32][33][34] A lattice model, called Limited Mobility, has been recently applied to study the influence of additives on the mobility of a matrix and the consequent change in the polymer T g . 26 The authors showed that both additive concentration and their molecular properties, such as stiffness, determine whether the T g of the system is raised or lowered respected to the pure material.…”
Section: Introductionmentioning
confidence: 99%
“…The MD-predicted density and total HSP values in Table can also be compared to previous work. As noted earlier, Li et al employed the Polymer Consistent Force Field (PCFF) for all-atom MD simulations of plasticized PVC; they report density and solubility parameters at 300 K and 1 atm for homogeneous systems of atactic PVC (ρ: 1.36 g/cm 3 , δ t : 16.50 MPa 1/2 ) and several different plasticizers, including DEHP (ρ: 0.948 g/cm 3 , δ t : 19.46 MPa 1/2 ) and DEHT (ρ: 0.951 g/cm 3 , δ t : 18.74 MPa 1/2 ) . When comparing these selected PCFF-predicted values to the present GAFF-predicted values, the percent difference, (value 1 – value 2 )/average­(value 1 , value 2 ) × 100%, ranges from 1.29 to 2.87% (density) and 2.76 to 32.06% (total HSP).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, AA-MD was used to systematically investigate the influence of plasticizer chemistry (DEHP and five different di-iso phthalates with 4 to 13 alkyl carbons) on the properties of plasticized atactic PVC, such as density, T g , Hildebrand solubility parameter, enthalpy of mixing, radial density distributions, mobility/diffusivity based on mean-square displacement vs time, and uniaxial tensile modulus . This AA-MD work was later extended by the same researchers to several additional plasticizers, including DEHT, citrates, trimellitates, and aliphatic dicarboxylates, for a total of 14 different plasticizers . In a separate study, AA-MD was used to investigate the influence of 11 different plasticizers, including DEHP, levulinates, succinates, an adipate, and an oleate, on PVC based on glass-transition temperature, Flory–Huggins interaction parameters, and mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar relationship was observed with linear succinate diester plasticizers as the largest improvement in tensile properties was observed for plasticizers functionalized with alkyl chain lengths between four and seven carbons. 38 The complex relationship between chemical structure and plasticizer efficiency is one which has been studied both practically and computationally by many academic groups, 23,42,43 and highlights the challenge of striking a fine balance between polar and nonpolar functional groups on the plasticizer molecule. The polar functional groups are essential to compatibilize the plasticizer with the polar PVC backbone and serve as hydrogen-bond acceptors, while the nonpolar groups disrupt the PVC chain-chain interactions and increase the free volume of polymer matrix 44 (for a more in-depth discussion on this topic as well as additional theories of plasticization, we direct the readers to the works of Daniels and Mascia).…”
Section: Mechanical Propertiesmentioning
confidence: 99%